Indian Knowledge Systems and Environmental Conservation - Dr.Poornendra Prakash Shukla; Dr. Ashish Yadav (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The Indian Knowledge Systems (Bhartiya Gyan Parampara) represents a comprehensive framework developed over millennia, emphasizing harmony between human civilization and the natural world. This research paper explores the intrinsic connection between Systemsal Indian knowledge systems and environmental conservation, demonstrating how ancient ecological principles remain profoundly relevant to contemporary sustainability challenges. Through analysis of philosophical foundations, Systemsal practices, and case studies, this paper argues that integration of Bhartiya Gyan Parampara with modern environmental science offers a holistic pathway to address climate change, biodiversity loss, and resource degradation. The study reveals that concepts such as Vasudhaiva Kutumbakam (the world is one family), Vrikshayurveda (tree science), sacred groves, and Systemsal water harvesting systems embody sophisticated ecological understanding that preceded modern conservation theory by centuries[1]. This paper advocates for the recognition and integration of Indian knowledge Systemss into contemporary environmental policy and practice.